THE EFFECT OF PRICE DISCOUNT, BONUS PACK, AND IN-STORE DISPLAY ON IMPULSE BUYING DECISIONS - Sumardin; Rini Elfina; Rahmad Budi Harto; Nurmayunita (LPPM Universitas Ibnu Sina, 2022)
The behavior of a person when buying can be said to be unique and different. The purpose of this study was to obtain a name, advertisement and country of origin based on customer opinion. The population in this study was 966 customers of Carrefour Riau Islands Batam. The sample consisted of 91 respondents, who were randomly assigned to sample. Data analysis uses multiple regression tests and imagination and uses the SPSS 23 model. Brand, promotion and country of origin variables then simultaneously have a significant effect on consumer attitudes